Irinotecan‐induced severe hypotension in a patient with lung cancer. Issue 4 (21st April 2022) - Nakano, Ryota; Momo, Kenji; Matsuzaki, Airi; Sakai, Akiko; Uchikura, Takeshi; Tanaka, Katsumi; Numazawa, Satoshi; Sasaki, Tadanori
Abstract: Most hypotension during chemotherapy is caused by an allergic mechanism. Conversely, non‐allergic hypotension due to chemotherapy is rare. In this case report, we present a patient who suffered severe hypotension followed by the administration of irinotecan‐based chemotherapy and some supportive care such as steroids for preventing emesis. A 71‐year‐old man with hypertension was diagnosed with stage IV small cell lung cancer (sT1cN3M0). Severe hypotension occurred in the patient after every administration of chemotherapy. Finally, he was able to receive all four courses of chemotherapy as planned along with the medical staff's support care. This case provides that a regimen that contained irinotecan and steroid could cause hypotension and the mechanism is partially explained by inhibiting choline esterase and adrenal insufficiency. We should be careful about non‐allergic hypotension when we administer irinotecan‐based chemotherapy. Abstract : We should be careful about non‐allergic hypotension when we administer irinotecan‐based chemotherapy.